Controle democrático no capitalismo contemporâneo: limites e contradições - Costa, Neila Karla Fernandes da (2012)
This study examines the determinations of the structural crisis of capital in the democratic control effected on the councils of rights and policies. Therefore the research aimed to apprehend and analyze the conjunctural and structural determinations and cyclical changes that incide on democratic control established by the Federal Constitution of 1988. The specific objectives turned to: (1) identify and analyze the theoretical and political fundamentals of democratic control in the production of social service in ENPESS 2010, in the productions of CFESS and the journal social services and society, (2) apprehend and analyze the possibilities, limits, contradictions and social direction of democratic control in contemporaneity and (3) identify and analyze the major political forces that constitute support and opposition to the exercise of democratic control. To approximate to the intended objectives the way theoretical and methodological covered was based in a perspective of totality that allows the apprehension of the object of study in their contradictory dimensions of universality, particularity and singularity. The results enabled to develop critical analysis of theoretical production of the Brazilian social service on the subject, having as snip studies of the journals social service and society; works of ENPESS 2010 and CFESS positioning. It was found, so in analysis undertaken, the spaces of democratic control suffer inflections of capital that shape their practices and social direction. In theoretical productions chosen, identified the prevalence of democratic control studied under an endogenous perspective to participatory canals, with incipient connections to the structural/conjunctural determinations of a historical period of crisis and seeks to restore the hegemony of capital. The positioning of the CFESS tends to recognition of democratic control in its contradictory dynamics recognizing the limits imposed by the sociability of the capital at the present time